Implementation of Integrated Farming System Technology Towards Sustainable Agriculture in the Kemiren Tourist Village, Banyuwangi - Parmawati S.P., M.E., Rita; Yanti, Indah; Ramadhani, Ayu Winna; Risvita, Wuwun; Achsin, Muhaimin Zulhair; Rahmawati, Nadhea Oktaviantina; Gunawan, Fahdynia Karnira; Ashari, Fadhil Muhamad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Kemiren Village, Glagah District, Banyuwangi Regency is a tourist village where the majority of people work as farmers. Several problems arise starting from the narrowness of agricultural land which has been converted into lodging buildings and places to eat. The lack of farmers' knowledge of agricultural technology to process plants is a factor in reducing the production capacity of rice plants. The purpose of implementing this community service activity is to increase motivation to create healthy and sustainable agriculture and provide knowledge and skills in processing local resources into a system and product that has high economic value. The results obtained are integrated farming system as well as products from IFS such as chicken eggs, rice, vegetables and catfish which are healthy and of good quality because they use organic ingredients.